Forest understorey communities respond strongly to light in interaction with forest structure, but not to microclimate warming. Issue 1 (2nd November 2021) - De Pauw, Karen; Sanczuk, Pieter; Meeussen, Camille; Depauw, Leen; De Lombaerde, Emiel; Govaert, Sanne; Vanneste, Thomas; Brunet, Jörg; Cousins, Sara A. O.; Gasperini, Cristina; Hedwall, Per‐Ola; Iacopetti, Giovanni; et al.
Summary: Forests harbour large spatiotemporal heterogeneity in canopy structure. This variation drives the microclimate and light availability at the forest floor. So far, we do not know how light availability and sub‐canopy temperature interactively mediate the impact of macroclimate warming on understorey communities. We therefore assessed the functional response of understorey plant communities to warming and light addition in a full factorial experiment installed in temperate deciduous forests across Europe along natural microclimate, light and macroclimate gradients. Furthermore, we related these functional responses to the species' life‐history syndromes and thermal niches. We found no significant community responses to the warming treatment. The light treatment, however, had a stronger impact on communities, mainly due to responses by fast‐colonizing generalists and not by slow‐colonizing forest specialists. The forest structure strongly mediated the response to light addition and also had a clear impact on functional traits and total plant cover. The effects of short‐term experimental warming were small and suggest a time‐lag in the response of understorey species to climate change. Canopy disturbance, for instance due to drought, pests or logging, has a strong and immediate impact and particularly favours generalists in the understorey in structurally complex forests.